Prevalence of Typhoid and Paratyphoid fever in a tertiary care hospital of Kathmandu valley - Gautam Kirtika (Journal of Diseases, 2023)
Typhoid or enteric fever is caused by Salmonella serotype typhi and paratyphi. It is one of the major public health problem in developing countries including Nepal. In recent years, increased urbanization and growing population within Kathmandu valley, attributed mainly to improper sanitary condition and fecal contamination of drinking water. These all factors contributes to a very high prevalence of typhoid fever through out the country. Methods This study was laboratory based study carried out six month period from march 2017 to August 2017 at microbiology lab in Nepal Medical college. Results and conclusion In the present study, the prevalence of enteric fever is mainly caused by Salmonella. Typhi than Salmonella Paratyphi A was observed.
Keywords: Enteric fever